Six Minute Walk Distance and Reference Equations in Normal Healthy Subjects of Nepal - Shrestha, S.K.; Srivastava, B. (Kathmandu University Medical Journal, 2017)
Background The self-paced six minute walk test is a simple assessment for sub-maximal functional capacity. It correlates well with sophisticated tests and gives good prediction for morbidity, mortality, quality of life and pulmonary functions. Objective To evaluate six minute walk distance in healthy adults to identify reference values and formulate reference equations. Method We conducted six minute walk test on 250 random volunteers at and above 18 years of age as per standard protocol. Age, gender, height and weight were measured. Pre-test and post-test vital parameters were recorded including pulse oximetry. The six minute walking distance was identified in all subjects. Multiple regression analysis was done to formulate regression equations to predict six minute walking distance. This also correlated age, gender, height, weight, body mass index with six minute walking distance. Result The mean six minute walking distance was 489±86 meters with males walking 509±82 meters and females 445±78 meters. Age, gender, weight and body mass index had significant contribution for prediction of six minute walking distance. Gender was the single most important predictor. Height had the least significance. Depending on coefficients of these variables we formulated three regression equations and tested them for accurate prediction. The two best equations were identified as: Predicted SMWD = 395–1.5xAge+2.47xWT–35.89xGender and Predicted SMWD = 440–1.82xAge–53.07xGender+5.12xBMI. Conclusion Gender, age and height are the most important predictors of six minute walking distance. Reference values and equations for both genders, different age groups with varying weights were derived for local population.